Transcriptomic analysis of the role of RasGEF1B circular RNA in the TLR4/LPS pathway - Ng, W.L.; Marinov, G.K.; Chin, Y.M.; Lim, Y.Y.; Ea, C.K. (Nature Publishing Group, 2017)
Circular RNAs (circRNAs) have recently emerged as a large class of novel non-coding RNA species. However, the detailed functional significance of the vast majority of them remains to be elucidated. Most functional characterization studies targeting circRNAs have been limited to resting cells, leaving their role in dynamic cellular responses to stimuli largely unexplored. In this study, we focus on the LPS-induced cytoplasmic circRNA, mcircRasGEF1B, and combine targeted mcircRasGEF1B depletion with high-throughput transcriptomic analysis to gain insight into its function during the cellular response to LPS stimulation. We show that knockdown of mcircRasGEF1B results in altered expression of a wide array of genes. Pathway analysis revealed an overall enrichment of genes involved in cell cycle progression, mitotic division, active metabolism, and of particular interest, NF-κB, LPS signaling pathways, and macrophage activation. These findings expand the set of functionally characterized circRNAs and support the regulatory role of mcircRasGEF1B in immune response during macrophage activation and protection against microbial infections.